Effects of carboxyl and aldehyde groups on the antibacterial activity of oxidized amylose. (15th July 2018) - Zi, Yaxin; Zhu, Mingjin; Li, Xinying; Xu, Yongbin; Wei, Hao; Li, Defu; Mu, Changdao
Highlights: Carboxyl group gave oxidized amylose antibacterial activity through pH-lowering effect. Aldehyde group contributed antibacterial activity by damaging bacterial cell outer membrane. Dialdehyde-carboxyl-amyloses presented the most efficient antibacterial activity. Carboxyl group acted as a synergistic group against bacteria with aldehyde group. Abstract: Dialdehyde-amyloses, dicarboxyl-amyloses and dialdehyde-carboxyl-amyloses with different oxidation levels were prepared and used to study the effects of aldehyde and carboxyl groups on the antibacterial activity of oxidized amyloses. The results showed that dicarboxyl-amyloses presented antibacterial activity through acidic pH effect produced by carboxyl groups, which was easily reduced or eliminated by adjusting pH. Dialdehyde-amyloses possessed a broad-spectrum antibacterial activity owing to the reactivity of aldehyde groups rather than acidic pH effect. Aldehyde would irreversibly damage bacterial cell wall and cytoplasmic membrane, resulting in decay and death of bacterial cells. It is interesting that the antibacterial properties of dialdehyde-carboxyl-amyloses were improved to some extent compared to dialdehyde-amyloses. The improvement of antibacterial effect of dialdehyde-carboxyl-amyloses may be due to the increasing dispersibility endowed by carboxyl groups, which could effectively enhance the interaction between dialdehyde-carboxyl-amyloses and bacteria. As a result, carboxyl group could act as a promising synergistic group against bacteria with aldehyde group.